2021
DOI: 10.1093/jac/dkab250
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription policy for acute otitis media: do we follow the guidelines?

Abstract: Background Acute otitis media (AOM) is a common cause for antibiotic prescription. Most guidelines endorse abstaining from immediate antibiotic treatment (‘watchful waiting’, WW) in mild–moderate episodes. We studied adherence rates to the latest AOM guidelines (2013), in terms of antibiotic type and prescription options. Methods In this population-based study, AOM episodes were identified in Clalit Health Services-insured ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Seven out of twelve papers reported the use of macrolides in a small proportion of cases, ranging from 1.3% to 10%. Marom et al [ 13 ] and Frost et al [ 19 ] reported that azithromycin was the preferred macrolide in population samples with AOM from Israel and the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Seven out of twelve papers reported the use of macrolides in a small proportion of cases, ranging from 1.3% to 10%. Marom et al [ 13 ] and Frost et al [ 19 ] reported that azithromycin was the preferred macrolide in population samples with AOM from Israel and the United States.…”
Section: Resultsmentioning
confidence: 99%